EDUCATIONAL DECENTRALIZATION AND ISLAMIC EDUCATION POLICY IMPLEMENTATION IN WEST SUMATRA, INDONESIA - Sandra, Ika; Rama Arya Kurniawan; Muhammad Alfian (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the governance and implementation of Islamic education within Indonesia’s decentralized education system, focusing on West Sumatra, particularly the cities of Padang and Padang Panjang. The transition from a centralized to a decentralized governance structure in 1999 granted local governments greater authority over educational management, enabling them to adapt policies to local socio-religious contexts. This research explores the role of local governments in managing Islamic education across different types of institutions, including public schools, Islamic boarding schools, and pesantren. Adopting a qualitative research design, data were collected through in-depth interviews with key stakeholders such as education officials, school principals, and teachers—as well as through document analysis of relevant government and institutional policies. The findings reveal varied approaches to the implementation of Islamic education across institutional types, reflecting differences in governance structures, curricular integration, and religious orientation. The study also identifies key challenges faced by local authorities, particularly in balancing national curriculum requirements with local Islamic values and institutional autonomy. Despite these challenges, educational institutions demonstrate considerable flexibility and adaptability in responding to decentralization policies. This research highlights the dynamic interaction between policy, local governance, and religious values in shaping the practice of Islamic education in West Sumatra.